Vintage marketing differentiation : the origins of marketing and branding strategies - Williams, Robert L., Jr; Williams, Helena A. (Palgrave Macmillan, 2017)
This book analyzes the origins of marketing and branding strategies and the unique situations involving differentiation. Photographs of actual materials that were created and used in marketing campaigns between 1846-1946 are featured to bring to life these vintage innovations. Examining how and why these classic strategies were devised and implemented provides insight on how the vintage strategies can continue to be used to position products, services, and experiences within current market situations. Vintage Marketing Differentiation describes real life, innovative, outside-the-box solutions. It explains a marketing differentiation process and emphasizes the critical nature of the perception of trends and timely action. Profiles of over 30 companies and brands depict nearly 20 categories of the first marketing strategies ever to be used. These powerful strategies ignited competitive advantages and help explain why most of these companies are still in business today!- Resumé vydavatel
Keywords: marketing -- dějiny; marketing -- history; branding (marketing); elektronické knihy; monografie; electronic books; monographs